Risk factors of anaphylaxis in Korea: Identifying drug-induced anaphylaxis culprits using big data. Issue 35 (2nd September 2022) - Ahn, Kyung-Min; Kim, Byung-Keun; Yang, Min-Suk
Abstract : Drug-induced anaphylaxis is a fatal medical condition whose incidence has been increasing continuously. Due to differences between genetic backgrounds and health care systems, different populations may be prone to various causative drugs. Using the Health Insurance Service and Assessment Service database, we investigated culprit drugs for drug-induced anaphylaxis and common medication risk factors in the Korean general population. We collected medical prescription histories within 3 days prior to anaphylaxis between January 2011 and December 2019 from the HIRA database. Designed as a case-crossover study, the attributable visits (case visits) were matched to medical visits (control visits) with the drug sets for each visit. We collected a list of medication risk factors for anaphylaxis and calculated the risk ratio of each agent using the chi-square test and conditional logistic regression analysis. A total of 159, 473 individuals were listed in the database with a diagnosis of anaphylaxis in the HIRA from 2011 to 2019. After evaluating the suitability of control visits for matching with a case visit, 8168 subjects and 767 drugs were analyzed. The chi-square analysis identified 31 drugs as potential risk factors for drug-induced anaphylaxis in Korea. After applying a conditional logistic regression analysis for each agent, 5 drugs were found to be the common medication risk factors for drug-induced anaphylaxis: cefaclor, iopromide, iohexol, iomeprol, and tolperisone. We found 5 medication risk factors that showed the highest risk of drug-induced anaphylaxis and their degree of risk using an objective methodology in the Korean general population.